The effect of race and gender on bail outcomes: A test of an interactive model - Katz, Charles M. (American journal of criminal justice, 1995)
This paper responds to suggestions that researchers interested in the relationship between defendant race, defendant gender, and criminal justice outcomes broaden their focus to include pretrial decision making. We used data on defendants charged with violent felonies in Detroit Recorder’s Court to analyze the effect of race and gender on the amount of bail imposed by the judge and on the defendant’s pretrial status. We found that judges take gender, but not race, into account in determining the amount of bail for certain types of cases; more specifically, Black females faced lower bail than Black males in less serious cases. In contrast, we found that both race and gender affected the likelihood of pretrial release. White defendants were more likely than black defendants to be released pending trial and females were more likely than males to be released prior to trial. In fact, white females, white males, and black females all were more likely than black males to be released.